(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2018)
Street trading provides economic venture and livelihood activity for coping daily in the urban areas among street trading operators in profit zones of motor parks with noticeable defacing structures, waste generation and poor waste management. Therefore, this study examined the practices and attitude of street traders to sanitary environment in Ibadan metropolis. Snow balling, purposive and random sampling techniques were used to select 120 respondents for the study; data were collected using structured interview schedule, frequency counts, percentages, chi-square and Person Product Moment Correlation. More than half (54.2%) of the respondents were females, mean age of 33 years, 42.5% married, 51.7% had no formal education and 40% had a monthly income of ₦19,001-₦29,000. Verbal announcement of goods to passengers and passerby (93.3%) was the most street trading practice, more than half (58.5%) of the respondents had poor attitude towards sanitary practices, with many (65.0%) of the respondents always dropping waste on the road side for street cleaners to collect. Untimely collection of wastes from the motor park (80.8%) was the most severe constraint to sanitary practice. Educational level (χ 2=19.006), years of street trading (χ 2=17.001), street trading practices (r=0.214), attitude of respondents to street trading (r=0.601) and constraints to sanitary practices (r=0.406) were significantly related to sanitary practices undertaken by the respondents. Hence, more enlightenment programmes of the respondents on proper waste management is of essence and efficiency of waste management officers to quick collection of wastes as concerted efforts for sustainable good sanitary practices in the motor parks.